Pendampingan Kelompok Tani Desa Batu Kerbuy dalam Pembuatan Pestisida Nabati - Afriani, Ferina; Anam, Khoirul; Aliyah, Siti; Ariyani, Aminah Happy Moninthofa (Jurnal Ilmiah Pangabdhi, 2025)
Batukerbuy Village is a coastal village located in Pasean District, Pamekasan Regency. The main commodity in this village is chili. However, there are obstacles that can cause damage to chili plants, namely the whitefly pest attack. Whitefly pests suck sugar-containing plant fluids, called sap, from plant parts such as leaves, stems, and flowers. This pest attack can cause huge losses for farmers so there must be proper handling to overcome the pest attack. The use of chemical pesticides is considered to have a negative impact on humans and the environment. One alternative to pest control to be developed is the manufacture of vegetable pesticides using neem leaves. Neem leaves contain alkoids, steroids, saponins, tannins, and flavonoids. Therefore, socialization and training on making vegetable pesticides were conducted with the aim of reducing the use of chemical pesticides. The results of this socialization include an understanding of the importance of sustainable agriculture, where the use of vegetable pesticides can be a better solution in controlling plant pests.